TEAMWORK IN ACTION: ADVANCING STUDENT DEVELOPMENT THROUGH COOPERATIVE LEARNING STRATEGIES IN PHYSICAL EDUCATION - Li, Wang Jie; Chen, Li Hua (Research Journal of Education and Allied Studies, 2024)
Cooperative learning is a pedagogical approach widely applied in various educational contexts, with particular relevance in the domain of physical education. This approach's practical value in physical education has gained significant recognition. College and university-level physical education instruction aims to enhance students' physical fitness, stimulate their intrinsic motivation for participating in physical activities, and thereby promote their holistic development and wellbeing. However, several challenges persist in the effective application of cooperative learning within the realm of college physical education instruction. Enhancing the quality of physical education teaching and refining the utilization of cooperative learning pedagogy has emerged as a pivotal concern for physical education educators in higher education.